Media E-Learning Application Strategic PLADACYS: Planning, Design, and Action to Corporate Analysis-Based Android In the Strategic Management Course - Elfia Nora; Syhabudhin Syhabudhin; I Nyoman Suputra (Universitas Negeri Malang, 2021)
Strategic Management, is a course that must be taken by all undergraduate students majoring in Management at the Faculty of Economics. And during this learning model that is applied face-to-face lecturers still often only use PPT media and provide tasks directly. The goal of the development of media e-learning Application Strategic PLADACYS (Planning, Design, and Action to Corporate Analysis-Based Android) in this strategic management course is to create and develop more innovative electronic learning media and provide more interactive learning media to students adjusting to the free learning curriculum. Millennials are referring to technology. Learning tools developed in the form of e-learning media that can be installed on Android in the form of Strategic Planning analysis (SPA) menu, Strategic design analysis (SDA), Strategic action analysis (SAA) menus and menus in this application will contain a grouping of materials, tasks, and practices of strategic management lectures by following the symbol menu (SPA) Theory for planning, designing strategies with analytical tools. (SDA) and looking for data to the company or industry as well as the practice of knowing the determinants of the company's success and analyzing (SAA). The development method carried out is the Borg &Gall development model [1] using waterfall grooves(waterfall)at the stage of development. The development stages begin with needs analysis, product planning, product development, trial/implementation (validation), revision, and report creation. The product results in the form of Application Strategic PLADACYS (Planning, Design, and Action to Corporate Analysis-Based Android) as a learning medium in strategic management courses, and will be equipped with media application videos, as well as media usage instructions.